Harvard business review on thriving in emerging markets. (Boston, Mass. : Harvard Business Review Press, 2011)
"If you need the best practices and ideas for gaining market share in developing economies--but don't have time to find them--this book is for you. Here are 10 inspiring and useful perspectives, all in one place. This collection of HBR articles will help you: - Manage risk in unstable environments - Ward off political threats to your business - Customize your business model for emerging markets - Tailor your strategy to capitalize on countries' strengths - Gain ground on emerging giants - Compete in China's new high-tech market - Win the war for talent in developing economies - Serve the bottom of the pyramid profitably."--GoogleBooks.
New Business Models In Emerging Markets / Matthew J. Eyring, Mark W. Johnson, and Hari Nair -- China vs the World / Thomas M. Hout and Pankaj Ghemawat -- Is It Too Late to Enter China? / Edward Tse -- How Local Companies Keep Multinationals at Bay / Arindam K. Bhattacharya and David C. Michael -- China + India: The Power of Two / Tarun Khanna -- The Battle for Female Talent in Emerging Markets / Sylvia Ann Hewlett and Ripa Rashid -- Making Better Investments at the Base of the Pyramid / Ted London -- Strategies That Fit Emerging Markets / Tarun Khanna, Krishna G. Palepu, and, Jayant Sinha -- The Hidden Risks in Emerging Markets / Withold J. Henisz and Bennet A. Zelner -- Managing Risk in an Unstable World / Ian Bremmer.
Includes index.
Description based on print version record.
Keywords: International business enterprises -- Developing countries; International trade; Emerging Market; Kapitalanlage; Commerce international -- Nouveaux pays industrialisés; Entreprises multinationales -- Chine; Stratégie -- Commerce -- Nouveaux pays industrialisés; Commerce; International business enterprises; International trade; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Developing countries -- Commerce; Entwicklungsländer; Developing countries; elektronické knihy; electronic books